2010 11th International Conference on Control Automation Robotics &Amp; Vision 2010
DOI: 10.1109/icarcv.2010.5707242
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of a path following controller for planar snake robots

Abstract: Abstract-This paper considers path following control of snake robots along straight paths. A controller is proposed which, under the assumption that the forward velocity of the snake robot is nonzero and positive, guarantees K-exponential stability of the distance between the snake robot and the desired path and also K-exponential stability of the heading of the robot with respect to the direction of the path. The performance of the path following controller is investigated through experiments with a physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…For equation (13), if the mass matrix M is singular, the Udwadia-Phohomsiri 27 equation should be used instead of Udwadia-Kalaba 29 equation to acquire the equation of motion of the constrained system, and the equation of motion becomes…”
Section: Dynamics Of Udwadia-kalaba Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…For equation (13), if the mass matrix M is singular, the Udwadia-Phohomsiri 27 equation should be used instead of Udwadia-Kalaba 29 equation to acquire the equation of motion of the constrained system, and the equation of motion becomes…”
Section: Dynamics Of Udwadia-kalaba Theorymentioning
confidence: 99%
“…Date et al, 6,7 Watanabe et al, 8,9 Hicks and Ito, 10 and Toyoshima et al 11 modeled the snake and studied the optimized torque control of the system on the basis of classical dynamic theories. Lijieback et al [12][13][14] achieved the trajectory tracking controller design for the snake robot. Alamir et al 15 and El Rafei et al 16 designed feedback control scheme and sliding mode control scheme for snake-like eel robot.…”
Section: Introductionmentioning
confidence: 99%
“…Other approaches to achieving planar locomotion include Chernousko's study of a 3-link snake robot, in which the joint angles are made to perform "elementary motions" from which more complex gaits can be built [37]. Liljebäck et al demonstrated a path following control scheme and waypoint guidance in a snake robot approximating the serpenoid curve, both in simulation and experimentally [38]- [39]. Liljebäck et al also proved that anisotropic ground friction is a necessary condition for controllable locomotion, developed a simplified model of serpentine locomotion consisting of only translational motions, and tested jamming resolution schemes during interaction with obstacles [40]- [41].…”
Section: Modeling and Control Of Snake Robotsmentioning
confidence: 99%